Adolescent HIV/AIDS: Issues and challenges - Naswa, Smriti (Medknow Publications, 2010)
Adolescence (10-19 years) is a phase of physical growth and development accompanied by sexual maturation, often leading to intimate relationships. Adolescent HIV/AIDS is a separate epidemic and needs to be handled and managed separately from adult HIV. The adolescents can be subdivided into student, slum and street youth; street adolescents being most vulnerable to HIV/AIDS. Among various risk factors and situations for adolescents contracting HIV virus are adolescent sex workers, child trafficking, child labor, migrant population, childhood sexual abuse, coercive sex with an older person and biologic (immature reproductive tract) as well as psychological vulnerability. The most common mode of transmission is heterosexual, yet increasing number of perinatally infected children are entering adolescence. This is due to “bimodal progression” (rapid and slow progressors) among the vertically infected children. Clinically, the HIV infected adolescents present as physically stunted individuals, with delayed puberty and adrenarche. Mental illness and substance abuse are important co-morbidities. The disclosure and declaration of HIV status to self and family is challenging and guilt in sexually infected adolescents and tendency to blame parents if vertically affected need special consideration and proper counseling. Serodiscordance of the twins and difference in disease progression of seroconcordant twins are added causes of emotional trauma. Treatment related issues revolve around the when and what of initiation of ART; the choice of antiretrovirals and their dosages; issues related to long term ADRs; sense of disinhibition following ART commencement; adherence and resistance.